Drug-Transporter Gene and Refractory Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The drug-transporter gene ABCB1 polymorphism (C to T) at position 3435 was typed in 315 patients with epilepsy, classified as drug-resistant in 200 and drug-responsive in 115, and 200 controls without epilepsy, in a study at the Institute of Neurology, London, UK.